MODERASI DAULAH RUSTAMIYYAH DALAM PENYELESAIAN KONFLIK POLITIK - Rofiq, Ahmad Choirul (Analisis: Jurnal Studi Keislaman, 2014)
MODERATE POLICY OF   DAULAH RUSTAMIYYAH IN RESOLVING    POLITICAL   CONFLICTS.    Disputes    due   to conflict  of interest  are unavoidable  phenomena   particularly  in political life. Political conflicts arise due to differences of opinion, competition, and conflicts between a number of individuals, groups, or organizations involving state officials. This paper seeks to uncover the pattern  of political  conflict resolution carried by Daula Rustamiyyah which incidentally belonged to Khawarij Ibadiyyah  moderate   wing.  By  using  the  historical   approach, the author  finds out   that  the  political  policy  of Rustamiyyah to resolve political  conflicts  within  the government  were based on Ibadiyyah doctrines  that  promote  moderation.  A number  of political  conflicts were successfully    resolved  by Rustamiyyah with a minimum violence. To solve political conflicts, the Rulers of Rustamiyyah  began with persuasive  step,   from admonition to  threat.   Then,  if  necessary,  it involves  a  third  party  as  a mediator. If the measures were all unsuccessful,  they took a firm stance,  especially  against  those  who endanger  public  stability. In addition,  the government  often  took  the initiative  to utilize diplomacy during the ongoing armed conflict. By implementing such policies, peace and stability can be maintained by the Rustamiyyah government.